The Sleeping Giant of Goll - Abbott, Tony.; Jessell, Tim (New York : Scholastic, 2000)
Neal and his friends must find a way to save Droon from a giant whom Lord Sparr has awakened.
"A Little Apple paperback."
4.2
3-6
Keywords: Good and evil. -- Fiction; Giants -- Fiction; Fantasy; Good and evil -- Fiction; Giants -- Fiction; Fantasy fiction